Managing cultural diversity and conflict in family businesses: An organizational perspective - Tanja Gavrić; Ivana Načinović Braje (Administrative Sciences, 2024)
This study aims to investigate the occurrence of conflicts in family businesses, particularly focusing on their impact on founder behavior and organizational culture. Conducted in Bosnia and Herzegovina, the research employs a qualitative methodology to gain an in-depth understanding of conflicts within family businesses. The study utilizes semi-structured interviews as the primary data collection tool, engaging with 5 founders and 12 successors across various family owned businesses. The sample, comprising 17 participants, offers diverse perspectives on conflict dynamics between founders and successors. The interviews, designed to explore recurring key themes, delve into the nature and characteristics of task and process-based disagreements within these family enterprises. Key findings from this study include the observation that task or process-based disagreements, commonly arising between family members, can act as catalysts for founders to re-evaluate their behavior, potentially influencing the shaping of the organizational culture. The research highlights the importance of fostering a culture of open communication, critical thinking, and respect within family firms. Such a culture can play a significant role in reducing relationship conflicts and aid in reaching constructive resolutions. Additionally, the study reveals that the features of organizational culture within family businesses can be instrumental in managing conflicts effectively. This research underscores the complexity of family relationships in business settings and emphasizes the necessity of examining these dynamics from multiple angles. Given the prevalence of family members in key positions within family firms, the study sheds light on the importance of addressing diversity and conflict among family members, considering their long-term implications on the culture and future of these firms.
Keywords: 350; conflict; diversity; family business; founder; organizational culture; successor